2020
DOI: 10.1136/heartjnl-2020-317265
|View full text |Cite
|
Sign up to set email alerts
|

Infective endocarditis at a tertiary care hospital in South Korea

Abstract: ObjectiveThe treatment of infective endocarditis (IE) has become more complex with the current myriad healthcare-associated factors and the regional differences in causative organisms. We aimed to investigate the overall trends, microbiological features, and outcomes of IE in South Korea.MethodsA 12-year retrospective cohort study was performed. Poisson regression was used to estimate the time trends of IE incidence and mortality rate. Risk factors for in-hospital mortality were identified with multivariable l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
16
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 30 publications
2
16
0
3
Order By: Relevance
“…Also, another study found that diabetes mellitus was the most common risk factor (18.2%) for IE. 19 In this study the culture positive IE patients were 46 (76.6%) and culture negative IE patients 14 (23.4%). In contrast, a previous study revealed that culture positive IE patients accounted for 30.3% and culture negative for 69.7%.…”
Section: Discussionmentioning
confidence: 55%
“…Also, another study found that diabetes mellitus was the most common risk factor (18.2%) for IE. 19 In this study the culture positive IE patients were 46 (76.6%) and culture negative IE patients 14 (23.4%). In contrast, a previous study revealed that culture positive IE patients accounted for 30.3% and culture negative for 69.7%.…”
Section: Discussionmentioning
confidence: 55%
“…Second, as the epidemiology of IE may vary regionally, our conclusion based on single-institutional data may not be generally applicable. Still, we maintain our conclusion is sustainable regarding the main causative pathogens of IE are similar globally [ 24 , 34 ].Third, serologic assessment of non-culturable microorganisms like C . burnetii and Bartonella species was rarely performed in our study.…”
Section: Discussionmentioning
confidence: 58%
“…The protective effect of surgery for survival in patients with IE has been widely accepted by several authors [ 23 , 24 , 25 ]. Likewise, the benefit of surgical treatment in BCNIE has been suggested in a few studies.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, Q fever endocarditis was only confirmed in 6 cases. However, culture-negative endocarditis cases accounted for about a quarter of endocarditis cases in South Korea [26,27]. This suggests that Q fever endocarditis may be an underestimated disease in South Korea, and serological tests or PCR tests for C. burnetii should be more actively performed in cases of culture-negative endocarditis.…”
Section: Discussionmentioning
confidence: 99%